Identification and Evaluation of Pitfalls in the Migration From IEC 61131-3 to IEC 61499: A Review - Ashiwal, Virendra; Miguel-Escrig, Oscar; Wiesmayr, Bianca; Zoitl, Alois; Romero-Perez, Julio-Ariel (IEEE open journal of the Industrial Electronics Society, 2025)
The IEC 61131-3 standard was initially established to define a common software architecture and programming languages for programmable logic controllers (PLCs) produced by various manufacturers, leading to its widespread adoption since 1993. Since then, it has been a cornerstone in the industrial automation domain. Building upon this foundation, the IEC 61499 standard was developed to enhance the design and implementation of distributed control systems by incorporating advanced concepts from distributed systems and software engineering such as encapsulation, separation of control logic from communication infrastructure, and independent development of software components from their hardware deployment. While IEC 61499 introduces novel approaches, it also incorporates and extends key elements from IEC 61131-3, including function blocks, programming languages, and basic data types. Despite the advantages offered by the IEC 61499 standard, its adoption is still limited largely due to historical precedence, industry familiarity, better tool and vendor support, and the risk-averse nature of the industrial automation market. The migration or re-engineering effort from an existing IEC 61131-based automation system to IEC 61499 also faces challenges because it typically retains the underlying programming paradigms of IEC 61131-3. The contribution of this article is to identify the pitfalls associated with migrating PLC control code from IEC 61131-3-based automation systems to IEC 61499. For this purpose, we conducted a systematic literature review that address these identified migration pitfalls. We then synthesized the findings from the literature and provided a summary and research directions for addressing these pitfalls.